2012
DOI: 10.1007/s00429-012-0437-y
|View full text |Cite
|
Sign up to set email alerts
|

Common hippocampal structural and functional changes in migraine

Abstract: The hippocampus is classically involved in memory consolidation, spatial navigation and is involved in the stress response. Migraine is an episodic disorder characterized by intermittent attacks with a number of physiological and emotional stressors associated with or provoking each attack. Given that migraine attacks can be viewed as repeated stressors, alterations in hippocampal function and structure may play an important role in migraine pathophysiology. Using high-resolution magnetic resonance imaging, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
146
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(158 citation statements)
references
References 71 publications
9
146
3
Order By: Relevance
“…A myriad of behavioral changes observed in chronic pain patients, including elevated anxiety and depression (Gore et al 2012), problems in emotional decision making (Apkarian et al 2004;Gupta et al 2009), spatial working memory deficits (Abrahams et al 1999;Dick and Rashiq 2007;Kim et al 2012), and difficulty in classical conditioning tasks (Flor et al 2002), suggest abnormal hippocampal physiology in chronic pain. Indeed, some hippocampal functional changes have recently been identified in migraine pain (Maleki et al 2013), but investigations of hippocampal functional properties in the transition to chronic pain are completely absent.…”
mentioning
confidence: 99%
“…A myriad of behavioral changes observed in chronic pain patients, including elevated anxiety and depression (Gore et al 2012), problems in emotional decision making (Apkarian et al 2004;Gupta et al 2009), spatial working memory deficits (Abrahams et al 1999;Dick and Rashiq 2007;Kim et al 2012), and difficulty in classical conditioning tasks (Flor et al 2002), suggest abnormal hippocampal physiology in chronic pain. Indeed, some hippocampal functional changes have recently been identified in migraine pain (Maleki et al 2013), but investigations of hippocampal functional properties in the transition to chronic pain are completely absent.…”
mentioning
confidence: 99%
“…Based on our results, we detected that a long course of acupuncture treatment on active acupoints affected the hippocampus, which is associated with cognitive components of pain processing, as well as a major component of the human brain that links affective states with memory processing. The hippocampus was described as having increased gray matter volume in patients suffering chronic pain in a meta-analysis [47], and this was confirmed in a recent migraine study [6]. It seems to frequently participate in the central effects of acupuncture.…”
Section: The Difference In Resting-state Brain Activity Evoked By Actmentioning
confidence: 82%
“…Migraine has attracted more and more attention worldwide as a public health issue because of its high prevalence, frequent attack history, significant medical burden, and a serious reduction in quality of life (QOL) and productivity [2,3]. Although the exact mechanism of migraine is still unclear, there is plenty of neuroimaging evidence showing that migraine is a central nervous system disorder [4][5][6]. Our research group involving migraine without aura patients showed that abnormal structure and function was possibly associated with an impaired pain processing and modulatory process, such as in the anterior cingulate cortex (ACC), insula, basal ganglia, thalamus, supplementary motor area (SMA), prefrontal cortex, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we recently reported results of a structural analysis indicating lower hippocampal volume bilaterally in a mixed cohort of patients with fibromyalgia and fibromyalgia with comorbid insomnia (McCrae et al, 2015). However, not all authors have replicated these results in insomnia (Winkelman et al, 2010) or other pain-related conditions such as frequent migraines (Maleki et al, 2013) and osteoarthritis (Mutso et al, 2012). Furthermore, to our knowledge, no studies have addressed the potential impact of comorbid insomnia on hippocampal structure in patients with chronic musculoskeletal pain.…”
mentioning
confidence: 99%